Komodifikasi Tubuh Di Dalam Iklan New Era Boots - Ilmi Sila Ayu,; Rusdin, Febi Ramadhani (Jurnal Dakwah Tabligh, 2024)
Advertising has become an integral part of our lives, so that lifestyle and a wide choice in our lives are even unconsciously influenced by the messages that are suggested in the ad. However, advertising is often concerned with economic interests alone and the exclusion of moral values. Most advertising even considers the audience not as individuals but as units of consumption. That is just the target audience of consumers of the commodity traded in the advertising. By using the method of semiotic Roland Barthes, this study aims to determine the commodification of the body behind the ads New Era Boots. This study establishes the paradigm as a critical paradigm. Critical paradigm looking at the reality that there is a pseudo-reality as it is influenced by a variety of economic, political, and social power. While the theory used is the theory of the political economy of media, Lyotard. After conducting an analysis on the ads New Era Boots, the results of this study indicate a series of signifiers and signified either directly or indirectly contain elements of commodification. The series of markers that directly leads to the commodification is a sexy female model wearing skin-tight clothes and using models strapless clothes, exposing the body parts that provoke a craving audience watching it. In addition to clothing worn by a mini female model, tone of voice, and there is a wobble erotic sigh performed by a female model in television commercials, these New Era Boots clarify elements of the commodification of desire.